Strategi Komunikasi Persuasif dengan Metode Kisah dalam Meningkatkan Motivasi Belajar Mahasiswa Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang - Muhammad Randicha Hamandia; Abdur Razzaq (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2019)
Learning motivation is important for students to be able to learn well, precisely and directed. High learning motivation will bring students to achieve learning goals. This research aims to know how persuasive communication strategies with the story method in increasing student learning motivation of Islamic Broadcasting Communication of UIN Raden Fatah Palembang. This research uses qualitative. While the research subjects were 30 students of Isamic Broadcasting Communication of UIN Raden Fatah Palembang. From this research can be concluded that the persuasive communication strategy with the story method is an appropriate alternative in increasing student motivation of Islamic Broadcasting Communication of UIN Raden Fatah Palembang.